Can substituted allenes be highly efficient leaving groups in catalytic processes? a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Journal of Computational Chemistry, 2015)
There is considerable interest presently in the chemistry of allenes. The current computational investigation looks into the possibility of using allenes and their derivatives as leaving groups. As it is well known, leaving groups are significant in catalytic processes for generating the active site. A full quantum mechanical study using density functional theory shows that allenes and their derivatives can function as excellent leaving groups. Indeed, the calculations show that they can be several orders of magnitude more effective than existing ligands for this purpose. The modification of second generation Grubbs' catalysts with these ligands suggests that the allene ligand cases that would be most effective are those having electron withdrawing groups, especially those that have the potential for supramolecular interactions between the substituent groups in the free state. (c) 2015 Wiley Periodicals, Inc.
Keywords: allenes; carbones; Density functional theory; olefin metathesis; supramolecular interactions